2021
DOI: 10.3390/app11146625
|View full text |Cite
|
Sign up to set email alerts
|

Dam Deformation Interpretation and Prediction Based on a Long Short-Term Memory Model Coupled with an Attention Mechanism

Abstract: An accurate dam deformation prediction model is vital to a dam safety monitoring system, as it helps assess and manage dam risks. Most traditional dam deformation prediction algorithms ignore the interpretation and evaluation of variables and lack qualitative measures. This paper proposes a data processing framework that uses a long short-term memory (LSTM) model coupled with an attention mechanism to predict the deformation response of a dam structure. First, the random forest (RF) model is introduced to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…If two words are in a similar context, their semantics are also similar. erefore, the distributed representation of the vector is different from the discrete representation, which is a vector representation that uses a neural network to convert words into continuous values [13]. Researchers can represent the semantic similarity between…”
Section: Distributed Representationmentioning
confidence: 99%
“…If two words are in a similar context, their semantics are also similar. erefore, the distributed representation of the vector is different from the discrete representation, which is a vector representation that uses a neural network to convert words into continuous values [13]. Researchers can represent the semantic similarity between…”
Section: Distributed Representationmentioning
confidence: 99%
“…In recent years, a variety of machine learning architectures have been used in the field of dam safety monitoring, such as the autoregressive integrated moving average (ARIMA) algorithm [8], the support vector machine (SVM) algorithm [9], the artificial neural network (ANN) algorithm [10][11][12], and the random forest (RF) algorithm [13,14], etc. These algorithms can predict dam displacement with reasonable accuracy; among them, the ANN algorithm illustrates superior performance in dealing with nonlinear problems [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Salazar et al [25] detected abnormal values early by an enhanced regression tree, applying to a 100 m high arch dam. Su et al [26] used the density-based spatial clustering of applications with noise (DBSCAN) to identify and filter abnormal values of monitoring equipment and reduce random errors. Cheng et al [27] identified abnormal uplift pressure data of the gravity dam by the kernel density estimation method.…”
Section: Introductionmentioning
confidence: 99%